Analysis of reconstitution process, stability, stability of intravenous antibiotics in hospitalised patients in a private hospital - Kiki Amelia (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2024)
Introduction: reconstitution of sterile preparations is a series of changes in the drug from its original condition to a new product by dissolving or adding other ingredients carried out aseptically by the pharmacy. Aim: determine the suitability of the reconstitution technique, the suitability of stability (solvent type and solvent volume), and the suitability of the sterility of the reconstitution product. Methods: data collection obtained by observation is carried out with the help of a checklist that is adapted to hospital standard operating procedures (SOPs), Inject-able Drug Guide, guidelines for mixing inject-able drugs, and preparations. 48 processes of reconstitution of intravenous antibiotics were carried out in hospitals that could be observed as samples. Results: conformity to the preparation stage were 99%, the mixing stage was 73%, the labelling was 100%, and the labelling was 90%. In evaluating the stability of the solvent type category, the suitability of 100%. In the volume category of the solvent used, 90% were suitable, and 10% were unsuitable for the antibiotic’s cefotaxime 1 gram, vancomycin 1 gram, and sulbactam + ampicillin Na 1 gram. From the sterility test results, the reconstitution of ceftriaxone intravenous antibiotic preparations showed that the bacterial preparations were free of microorganisms (sterile). Conclusion: the personnel performing the reconstitution are nurses trained in intravenous antibiotic recovery. One of the factors that caused the reconstitution process not to be under the hospital's KSB was the lack of training and supervision from the hospital management. SPO recovery is not installed in an intravenous drug mixing room.